ANALYSIS THE EFFECTIVENESS OF BLENDED LEARNING MODEL DURING PANDEMIC COVID-19 FOR TENTH GRADE AT MA ASYIFA’ BATURAJA - Ariyani Victoria; Novarita Novarita; Trisilia Devana (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2021)
This study aims to find out the effectiveness of the blended learning model on reading skill for tenth grade at MA Asyifa’ Baturaja. This study used the qualitative descriptive research design. The population of this research was 19 students of Tenth grade at MA Asyifa’ Baturaja. The researcher took sample by used total sampling technique because the total population was less than 100 respondent. The data was collected by used questionnaire that consists of 20 statements that consist 0f 4 categories put forward by Keller, namely: Attention, Relevance, Confidence, and Satisfaction (ARCS). The researcher used descriptive statistics based on the percentages obtained from the result of recapitulation. Based on theory ARCS the researcher get the results, the attention percentage 64,4% in good category, relevance percentage 62% in good category, confidence percentage 66,75% in good category and satisfaction percentage 57,25% in fair category. From percentage of each category, the researcher get average 62,6% in the good category. The finding indicated that analysis the effectiveness of blended learning model on reading skill is good category, in sense blended learning is effective during pandemic Covid-19.